Hepatocellular carcinoma treated with sorafenib: early detection of treatment response and major adverse events by contrast‐enhanced US. (11th January 2013) - Sugimoto, Katsutoshi; Moriyasu, Fuminori; Saito, Kazuhiro; Rognin, Nicolas; Kamiyama, Naohisa; Furuichi, Yoshihiro; Imai, Yasuharu
Abstract Background & Aims Early prediction of tumour response and major adverse events (AEs), especially liver failure, in patients with hepatocellular carcinoma (HCC) is essential for maximizing the clinical benefits of sorafenib. To evaluate the usefulness of dynamic contrast‐enhanced ultrasound (DCE‐US) for the early prediction of tumour response and major AEs in HCC patients. Methods Thirty‐seven HCC patients were started on a reduced dosage of sorafenib, subsequently increased to the standard dosage. Tumour response at 1 month was assessed by CT using the Response Evaluation Criteria in Solid Tumors (RECIST). Major AEs were defined as grade 3 or higher. DCE‐US was performed before treatment (day 0) and on days 7, 14 and 28. Changes in perfusion parameters in the tumour and liver parenchyma between day 0 and later time points were compared between treatment responders and nonresponders based on RECIST and between patients who experienced major AEs and those who did not. Tumour results were also compared with progression‐free survival (PFS) and overall survival (OS). Results Tumour perfusion parameters based on the area under the time‐intensity curve (AUC) were statistically significant, with AUC during washin on day 14, the most relevant for tumour response (P = 0.0016) and AUC during washin on day 7, the most relevant for both PFS (P = 0.009) and OS (P = 0.037). A decrease in total AUC between days 0 and 7 in the liver parenchyma was strongly correlated with major AEs (P = 0.0002). Conclusion DCE‐US may be useful for the early prediction of tumour response and major AEs in patients with HCC.